Marital Quality Trajectory among Iranian Married Individuals: A Collectivist Perspective - Khodabakhsh AHMADI; Hassan SAADAT (Tehran University of Medical Sciences, 2015)
Background: The trajectory of marital quality over the life course assumes a curvilinear pattern and declines over time. However, most studies to date have been conducted in developed societies, leaving the generalizability of their findings open to skepticism. In this study, we aimed to delineate the trajectory of marital satisfaction in Iran. Methods: Using cluster-sampling method, representative sample of 800 Iranian married individuals from urban areas of seven provinces of Iran, between February and May 2011 was surveyed. Each cluster included 50 households. Sealed packages containing survey material were delivered to households. Self-administered surveys included a checklist collecting demographic and socioeconomic data, and the Comprehensive Marital Satisfaction Scale. Generalized additive models (GAM) were used to explicate the trajectory of marital satisfaction over marital duration. Results: A total of 644 complete questionnaires were returned (response rate: 80.5%). Average age of the participants was 40yr and average duration of marriage 17yr. The fitted GAM showed that marital satisfaction is highest at the beginning but drastically declines over the first 10yr. After arriving a nadir, the downward progression is reversed in the next 10-15yr, reaching a level comparable to the beginning. At 23-25yr, a second declining wave initiates and marital satisfaction steadily declines thereafter. The overall shape remains the same after adjustment for number of children, economic status, and retirement. Conclusion: Marital trajectory assumes a curvilinear pattern and has three periods of decline, stagnation, and decline. The shape of trajectory bears similarities to the observed patterns in the US but is distinct, nevertheless.    Keywords: Collectivist culture, Marital Quality, Marital Relationship over time, Marital Trajector